31P-MRS saturation transfer for assessing human hepatic ATP synthesis at clinical field strength - Marc Jonuscheit; Benedict Korzekwa; Michael Schär; Julian Mevenkamp; Stefan Wierichs; Pavel Bobrov; Theresia Sarabhai; Sabine Kahl; Michael Roden; Vera B. Schrauwen-Hinderling (European Radiology Experimental)
Abstract Background 31P-magnetic resonance spectroscopy (MRS) saturation transfer (ST) allows for noninvasive investigation of liver energy metabolism by assessing flux rates of adenosine triphosphate (ATP) synthesis. However, this technique has rarely been applied at clinical field strengths because of long examination times and contamination from muscle tissue. Our aim was to establish a new method to robustly assess ATP synthesis using a clinical scanner. Methods A prospective single-center study was performed (January 2023–August 2024) within the German Diabetes Study. We established a suitable 31P-MRS ST protocol, tested it in vitro and in vivo and assessed its reproducibility. We assessed the hepatic apparent spin-lattice relaxation time of inorganic phosphate ( $${T}_{1,Pi}^{{′} }$$ T 1 , P i ′ ), equilibrium forward rate constant ( $${k}_{f}$$ k f ), and forward ATP synthesis rate ( $${F}_{ATP}$$ F A T P ) in nine control volunteers (CON) (six females) and eight patients (five females) with type 1 diabetes (T1D) and compared differences by ANOVA. Results Reproducibility assessment in nine CON, aged 27 ± 4 years (mean ± standard deviation), yielded coefficients of variation for repeated measurements of 7.1% and 21.3% for $${T}_{1,Pi}^{{′} }$$ T 1 , P i ′ and $${k}_{f}$$ k f , respectively. Group comparison revealed higher hepatic $${k}_{f}$$ k f (0.34 ± 0.03 s-1 versus 0.16 ± 0.03 s-1; p = 0.001) and $${F}_{ATP}$$ F A T P (35.3 ± 3.5 mM/min versus 16.4 ± 3.5 mM/min; p = 0.002) in CON than in T1D, aged 42 ± 15 years, respectively. Conclusion This 31P-MRS ST method allowed for robust assessment of hepatic ATP synthesis at clinical field strength and was sensitive enough to detect differences between CON and T1D volunteers. Relevance statement Noninvasive methods to investigate hepatic energy metabolism are urgently needed to evaluate liver health while preventing unnecessary biopsies. For broad clinical applicability, the robustness shown by the proposed method at clinical field strength is crucial. Trial registration ClinicalTrials.gov: NCT01055093—Prospective study on diabetes mellitus and its complications in newly diagnosed adult patients (GDC), NCT01055093, Registered: 01/22/2010, https://clinicaltrials.gov/study/NCT01055093?term=NCT01055093&rank=1#study-overview . Key Points The proposed magnetic resonance spectroscopy method calculates hepatic ATP synthesis rates at clinical field strength. The protocol shows acceptable reproducibility and spectra without contamination from muscle. The method can detect differences between participants with type 1 diabetes and controls. Graphical Abstract